Adhesive sheet, laminate, optical device, and image display device
The adhesive sheet addresses the trade-off between reworkability and transparency by using a specific composition of crosslinkable (meth)acrylic copolymer, (meth)acrylic resin particles, and a crosslinking agent, achieving excellent reworkability and high transparency for optical applications.
Patent Information
- Application Number
- JP2021031057
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-26
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-02-26
AI Technical Summary
Existing adhesive sheets used in optical applications face a trade-off between reworkability and transparency, with the inclusion of particles to enhance reworkability often leading to increased haze and reduced transparency.
A pressure-sensitive adhesive sheet composed of a crosslinkable (meth)acrylic copolymer, (meth)acrylic resin particles, and a crosslinking agent, specifically formulated to achieve excellent reworkability and high transparency by controlling the composition and structure of the adhesive layer.
The adhesive sheet exhibits excellent reworkability, allowing for easy position adjustment and removal of foreign matter, while maintaining high transparency and strong adhesive strength after heating, making it suitable for optical applications.
Smart Images

Figure 0007669719000002 
Figure 0007669719000003 
Figure 0007669719000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive sheet, a laminate including the pressure-sensitive adhesive sheet, an optical device, and an image display device. [Background technology]
[0002] Conventionally, input devices used in combination with display devices such as liquid crystal displays (LCDs) or display devices such as touch panels have been widely used. In the manufacture of these display devices and input devices, a transparent adhesive sheet is used when bonding optical members. A transparent adhesive sheet is also used when bonding a display device and an input device.
[0003] After bonding optical components together with an adhesive sheet, there is a demand for re-bonding the adhesive sheet, that is, for reworking (re-peeling) the adhesive sheet in order to adjust the position of the optical components or to remove foreign matter such as air bubbles between the components. For this reason, development of adhesive sheets with improved reworkability is also underway. For example, Patent Documents 1 to 3 disclose a technology that can impart reworkability to an adhesive sheet by incorporating particles into the adhesive layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 239616 [Patent Document 2] JP 2015-3943 A [Patent Document 3] JP 2015-3944 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the techniques disclosed in Patent Documents 1 to 3 can impart reworkability to pressure-sensitive adhesive sheets, but the inclusion of particles increases haze and impairs transparency, limiting their use in optical applications. Although it is highly desirable for pressure-sensitive adhesive sheets to have both reworkability and transparency, it has not been easy to obtain a pressure-sensitive adhesive sheet that is both excellent in reworkability and highly transparent, since the two are in a trade-off relationship.
[0006] The present invention has been made in consideration of the above, and aims to provide an adhesive sheet that has excellent reworkability and high transparency, a laminate that includes the adhesive sheet, and an optical device and an image display device. [Means for solving the problem]
[0007] As a result of extensive research into achieving the above object, the present inventors discovered that the above object can be achieved by forming a pressure-sensitive adhesive sheet from specific components, and thus completed the present invention.
[0008] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 In a pressure-sensitive adhesive sheet formed from a cured product of a pressure-sensitive adhesive composition, The pressure-sensitive adhesive composition contains a crosslinkable (meth)acrylic copolymer (A), (meth)acrylic resin particles (C), and a crosslinking agent (D), The crosslinkable (meth)acrylic copolymer (A) is a polymer including (meth)acrylic ester units (a) having an alkyl group having 4 to 10 carbon atoms, monomer units (b) having a carboxy group and / or a hydroxyl group, and macromonomer units (c) having a methyl methacrylate unit; The crosslinkable (meth)acrylic copolymer (A) contains 50 to 95 mass% of the (meth)acrylic ester unit (a), 1 to 50 mass% of the monomer unit (b), and 1 to 15 mass% of the macromonomer unit (c), In an elastic modulus image taken of the surface in Peak Force Tapping mode using an atomic force microscope, there are 3 to 20 spherical or island-like areas with a higher elastic modulus than the surrounding areas within any 10 μm square area, A pressure-sensitive adhesive sheet that satisfies the following physical properties (1) and (2). Physical properties (1): The adhesive strength to glass 30 minutes after application, measured according to the adhesive strength measuring method described in JIS Z 0237, is 0.01 to 5 N / 25 mm. Physical properties (2): The adhesive sheet is attached to a glass plate and heat-treated at 100°C and 0.5 MPa for 30 minutes. The adhesive strength to glass measured according to the adhesive strength measuring method described in JIS Z 0237 is 10 N / 25 mm or more. Section 2 Item 2. The pressure-sensitive adhesive sheet according to item 1, wherein the macromonomer unit (c) has a number average molecular weight of 5,000 to 10,000. Section 3 3. The pressure-sensitive adhesive sheet according to item 1 or 2, wherein the (meth)acrylic resin particles (C) have an average particle size of 0.1 to 5 μm. Section 4 4. The pressure-sensitive adhesive sheet according to any one of items 1 to 3, wherein the refractive index difference between the crosslinkable (meth)acrylic copolymer (A) and the (meth)acrylic resin particles (C) is 0 to 0.05. Section 5 5. The pressure-sensitive adhesive sheet according to any one of items 1 to 4, wherein the crosslinking agent (D) comprises one selected from the group consisting of an isocyanate compound, an epoxy compound, and a metal chelate. Section 6 Item 6. A laminate comprising the pressure-sensitive adhesive sheet according to any one of items 1 to 5 and an adherend. Section 7 Item 7. An optical device comprising the laminate according to item 6. Section 8 Item 7. An image display device comprising the laminate according to item 6. Effect of the Invention
[0009] The pressure-sensitive adhesive sheet of the present invention has excellent reworkability and high transparency. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic diagram showing an example of an embodiment of a pressure-sensitive adhesive sheet with a release sheet. [Diagram 2] 1 is an example of an elastic modulus image taken of the surface of an adhesive sheet in Peak Force Tapping mode using an atomic force microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present invention will be described in detail. In this specification, the expressions "contain" and "include" include the concepts of "contain", "include", "consist essentially of" and "consist only of". In addition, in this specification, a numerical range expressed using "to" means a range including the numerical values written before and after "to" as the lower and upper limits.
[0012] 1. Adhesive sheet The pressure-sensitive adhesive sheet of the present invention is formed from a cured product of the pressure-sensitive adhesive composition. In other words, the pressure-sensitive adhesive sheet of the present invention is obtained by curing the pressure-sensitive adhesive composition.
[0013] The pressure-sensitive adhesive composition contains a crosslinkable (meth)acrylic copolymer (A), (meth)acrylic resin particles (C), and a crosslinking agent (D). In addition, the pressure-sensitive adhesive sheet of the present invention has 3 to 20 spherical or island-like areas having a higher elastic modulus than the surrounding areas within any 10 μm square area in an elastic modulus image photographed on the surface using an atomic force microscope (hereinafter also referred to as "AFM") in Peak Force Tapping mode, and has both physical properties (1) and (2) described below.
[0014] The pressure-sensitive adhesive sheet of the present invention has excellent reworkability (i.e., positioning ability) and high transparency. In addition to having an initial adhesive strength suitable for reworkability, the pressure-sensitive adhesive sheet of the present invention has a property that the adhesive strength can be increased by heating after bonding adherends together (so-called heat adhesion). This allows the pressure-sensitive adhesive sheet of the present invention to firmly bond adherends together.
[0015] <Crosslinkable (meth)acrylic copolymer (A)> The crosslinkable (meth)acrylic copolymer (A) is a polymer containing (meth)acrylic ester units (a) having an alkyl group with 4 to 10 carbon atoms, monomer units (b) having a carboxy group and / or a hydroxyl group, and macromonomer units (c) having a methyl methacrylate unit. Hereinafter, the (meth)acrylic ester units (a) having an alkyl group with 4 to 10 carbon atoms will be simply referred to as "(meth)acrylic ester units (a)", and the monomer units (b) having a carboxy group and / or a hydroxyl group will be simply referred to as "monomer units (b)". In addition, the macromonomer units (c) having a methyl methacrylate unit will be simply referred to as "macromonomer units (c)".
[0016] In addition, the "unit" and "monomer unit" in the (meth)acrylic ester unit (a) refer to a repeating unit constituting a polymer. In addition, the macromonomer unit also refers to a repeating unit constituting a polymer, but since the macromonomer itself is composed of a plurality of repeating units (segments), the entire segment is referred to as the "macromonomer unit."
[0017] In this specification, "(meth)acrylic" means "acrylic" or "methacrylic", "(meth)acrylate" means "acrylate" or "methacrylate", and "(meth)allyl" means "allyl" or "methallyl".
[0018] The (meth)acrylic ester unit (a) is a repeating unit derived from a (meth)acrylic ester compound having an alkyl group having 4 to 10 carbon atoms. Examples of the (meth)acrylic ester compound having an alkyl group having 4 to 10 carbon atoms include a wide variety of known (meth)acrylic ester compounds, and specific examples thereof include n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, and isodecyl (meth)acrylate. The (meth)acrylic ester compound having an alkyl group having 4 to 10 carbon atoms preferably does not have a hydroxyl group or a carboxy group.
[0019] In the (meth)acrylic ester unit (a), the alkyl group preferably has 4 to 8 carbon atoms, and more preferably 4 to 6 carbon atoms.
[0020] The (meth)acrylic ester unit (a) contained in the crosslinkable (meth)acrylic copolymer (A) may be of one type only, or may contain two or more types.
[0021] In the crosslinkable (meth)acrylic copolymer (A), the content of the (meth)acrylic ester unit (a) is 50% by mass or more and 95% by mass or less. In this case, the pressure-sensitive adhesive sheet can have the desired reworkability and transparency, and satisfies the physical properties (1) and (2). If the content of the (meth)acrylic ester unit (a) is less than 50% by mass, the initial adhesive performance (adhesive performance before heat treatment) of the pressure-sensitive adhesive sheet may deteriorate. In terms of the reworkability and transparency of the pressure-sensitive adhesive sheet being more easily improved, the content of the (meth)acrylic ester unit (a) in the crosslinkable (meth)acrylic copolymer (A) is preferably 55% by mass or more, more preferably 60% by mass or more, even more preferably 65% by mass or more, and particularly preferably 70% by mass or more. In addition, in order to more easily improve the reworkability and transparency of the pressure-sensitive adhesive sheet, the content of the (meth)acrylic ester unit (a) in the crosslinkable (meth)acrylic copolymer (A) is preferably 94 mass% or less, more preferably 93 mass% or less, even more preferably 92 mass% or less, and particularly preferably 90 mass% or less.
[0022] In the present invention, the content of each structural unit in the crosslinkable (meth)acrylic copolymer (A) can be considered to be equal to the amount of polymerizable monomer derived from the corresponding structural unit used when producing the crosslinkable (meth)acrylic copolymer (A).
[0023] The monomer unit (b) is a repeating unit derived from a monomer having a carboxy group and / or a hydroxyl group.
[0024] Examples of the monomer having a carboxy group include a wide variety of known polymerizable monomers containing a carboxy group, and specific examples thereof include acrylic acid and methacrylic acid.
[0025] Examples of the monomer having a hydroxyl group include a wide variety of known hydroxyl group-containing polymerizable monomers, and specific examples thereof include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, polyalkylene glycol mono(meth)acrylate, and the like.
[0026] The crosslinkable (meth)acrylic copolymer (A) may contain, as the monomer unit (b), both a monomer unit having a carboxy group and a monomer unit having a hydroxyl group, or may contain only one of them. When the monomer unit (b) contains both a monomer unit having a carboxy group and a monomer unit having a hydroxyl group, the content ratio of these is not particularly limited, and a desired pressure-sensitive adhesive sheet can be obtained at any content ratio.
[0027] In the crosslinkable (meth)acrylic copolymer (A), the content of the monomer unit (b) is 1% by mass or more and 50% by mass or less. If the content of the monomer unit (b) is less than 1% by mass, the initial adhesive performance (adhesive performance before heat treatment) of the adhesive sheet deteriorates, and if it exceeds 50% by mass, the initial adhesive strength of the adhesive sheet becomes too strong, and the desired reworkability cannot be obtained. In this case, the adhesive sheet can have the desired reworkability and transparency, and satisfies the physical properties (1) and (2). In terms of the adhesive sheet being likely to have excellent reworkability and transparency, the content of the monomer unit (b) in the crosslinkable (meth)acrylic copolymer (A) is preferably 1.5% by mass or more, more preferably 2% by mass or more, and even more preferably 2.5% by mass or more. In addition, in order to provide a pressure-sensitive adhesive sheet with excellent reworkability and transparency, the content of the monomer unit (b) in the crosslinkable (meth)acrylic copolymer (A) is preferably 40 mass % or less, more preferably 30 mass % or less, even more preferably 25 mass % or less, and particularly preferably 20 mass % or less.
[0028] The macromonomer unit (c) is a repeating unit derived from a methyl methacrylate macromonomer. The methyl methacrylate macromonomer is, for example, an oligomer or polymer composed of a plurality of methyl methacrylate units and having a polymerizable reactive group at the end or the like. Examples of such a methyl methacrylate macromonomer include a wide variety of known macromonomers. The methyl methacrylate macromonomer can be, for example, an oligomer or polymer obtained by polymerizing 3 to 500 units of methyl methacrylate. Examples of the polymerizable reactive group introduced into the methyl methacrylate macromonomer include an acryloyl group and a methacryloyl group. It is preferable that the polymerizable reactive group is introduced into the end of the methyl methacrylate macromonomer.
[0029] The number average molecular weight of the macromonomer unit (c) is preferably 5000 to 10000. That is, the number average molecular weight of the methyl methacrylate macromonomer is preferably 5000 to 10000. In this case, the reworkability of the pressure-sensitive adhesive sheet is easily improved, and the haze can be further reduced. The number average molecular weight of the methyl methacrylate macromonomer is a value measured by gel permeation chromatography (GPC) and calculated based on polystyrene standards. However, when using a commercially available methyl methacrylate macromonomer, if the manufacturer's guaranteed value or measured value of the number average molecular weight is known, that value is used as the number average molecular weight of the methyl methacrylate macromonomer.
[0030] The methyl methacrylate macromonomer can be produced, for example, by a known production method, or can be obtained from a commercially available product, etc. An example of a commercially available methyl methacrylate macromonomer is AA-6 manufactured by Toagosei Co., Ltd.
[0031] In the crosslinkable (meth)acrylic copolymer (A), the content of the macromonomer unit (c) is 1% by mass or more and 15% by mass or less. If the content of the macromonomer unit (c) is less than 1% by mass, the initial adhesive strength of the adhesive sheet becomes too large and the desired reworkability cannot be obtained, and if it exceeds 15% by mass, the adhesive strength after heating of the adhesive sheet is not expressed. In order to improve the reworkability and adhesive strength after heating of the adhesive sheet, the content of the macromonomer unit (c) in the crosslinkable (meth)acrylic copolymer (A) is preferably 2% by mass or more, more preferably 2.5% by mass or more, and even more preferably 3% by mass or more. In order to improve the reworkability and transparency of the adhesive sheet, the content of the macromonomer unit (c) in the crosslinkable (meth)acrylic copolymer (A) is preferably 14% by mass or less, more preferably 13% by mass or less, and even more preferably 12% by mass or less.
[0032] The crosslinkable (meth)acrylic copolymer (A) may contain other structural units other than the (meth)acrylic ester unit (a), the monomer unit (b) and the macromonomer unit (c) as long as the effect of the present invention is not impaired. Examples of other structural units include a wide variety of structural units derived from compounds copolymerizable with the (meth)acrylic ester compound. Specific examples of such compounds include (meth)acrylic ester compounds having 3 or less carbon atoms (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, etc.), (meth)acrylonitrile, vinyl acetate, styrene, vinyl chloride, vinylpyrrolidone, vinylpyridine, etc., and other examples include amino group-containing (meth)acrylic esters, glycidyl group-containing (meth)acrylic esters, and alkoxyalkyl group-containing (meth)acrylic esters.
[0033] When the crosslinkable (meth)acrylic copolymer (A) contains the other structural units, the content ratio is 15% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, based on the total mass of the crosslinkable (meth)acrylic copolymer (A). The crosslinkable (meth)acrylic copolymer (A) may be composed of only the (meth)acrylic ester unit (a), the monomer unit (b) and the macromonomer unit (c). In other words, when the content ratios of the (meth)acrylic ester unit (a), the monomer unit (b) and the macromonomer unit (c) in the crosslinkable (meth)acrylic copolymer (A) are X (mass%), Y (mass%) and Z (mass%), respectively, it is preferable that X+Y+Z=100.
[0034] In the crosslinkable (meth)acrylic copolymer (A), the order of arrangement of each constituent unit is not particularly limited, and for example, a random copolymer, a block copolymer, a graft copolymer, etc. can be formed. In particular, since the crosslinkable (meth)acrylic copolymer (A) has a macromonomer unit (c), it has a block portion resulting from the macromonomer unit, and for example, this block portion can become a branched chain in the crosslinkable (meth)acrylic copolymer (A). The presence of such a branched chain makes it easier for the block portion to have a microphase separation structure in the polymer, so that the initial adhesive strength of the pressure-sensitive adhesive sheet can be more effectively suppressed to a low level, and the adhesive strength after heating can also be increased. Therefore, it is preferable that the crosslinkable (meth)acrylic copolymer (A) has a structure having a branched chain resulting from the macromonomer unit, even though it is a random copolymer.
[0035] The weight average molecular weight of the crosslinkable (meth)acrylic copolymer (A) is not particularly limited. For example, the weight average molecular weight of the crosslinkable (meth)acrylic copolymer (A) is preferably 100,000 to 2,000,000, more preferably 200,000 to 1,500,000, in order to keep the initial adhesive strength of the adhesive sheet low while easily increasing the adhesive strength after heating. The weight average molecular weight of the crosslinkable (meth)acrylic copolymer means the value before crosslinking with a crosslinking agent described later. The weight average molecular weight of the crosslinkable (meth)acrylic copolymer (A) is a value measured by gel permeation chromatography (GPC) and calculated based on polystyrene standard.
[0036] The pressure-sensitive adhesive composition may contain only one type of crosslinkable (meth)acrylic copolymer (A), or may contain two or more types.
[0037] The method for producing the crosslinkable (meth)acrylic copolymer (A) is not particularly limited, and for example, the crosslinkable (meth)acrylic copolymer (A) can be obtained by a production method utilizing a known polymerization method. The crosslinkable (meth)acrylic copolymer (A) can also be obtained from commercial products, etc.
[0038] The refractive index of the crosslinkable (meth)acrylic copolymer (A) is not particularly limited. In order to increase the transparency of the pressure-sensitive adhesive sheet, the refractive index of the crosslinkable (meth)acrylic copolymer (A) is preferably 1.45 to 1.50, and more preferably 1.46 to 1.49.
[0039] The refractive index of the crosslinkable (meth)acrylic copolymer (A) referred to here indicates a value measured by Method A described in JIS K 7142 (2014) "Plastics - Determination of refractive index."
[0040] <(Meth)acrylic resin particles (C)> The (meth)acrylic resin particles (C) are a fine particle material containing a (meth)acrylic resin as a main component.
[0041] In the (meth)acrylic resin particles (C), the type of the (meth)acrylic resin is not particularly limited, and a wide variety of known (meth)acrylic resins can be exemplified. Examples of the (meth)acrylic resin include polymers of (meth)acrylic acid esters. Specific examples of such (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate, as well as the above-mentioned (meth)acrylic ester compounds having an alkyl group with 4 to 10 carbon atoms, hydroxyalkyl (meth)acrylates (the number of alkyl carbons is, for example, 2 to 10), and glycidyl (meth)acrylate. Among these, the (meth)acrylic resin is preferably a methyl (meth)acrylate polymer, in that it is easy to impart reworkability to the pressure-sensitive adhesive sheet and to reduce haze.
[0042] The (meth)acrylic resin in the (meth)acrylic resin particles (C) may be a homopolymer or a copolymer. When the (meth)acrylic resin is a copolymer, examples include polymers containing two or more of the above-mentioned (meth)acrylic ester units, and the (meth)acrylic resin may also be a copolymer of a (meth)acrylic ester and a polymerizable monomer other than the (meth)acrylic ester. Examples of the polymerizable monomer other than the (meth)acrylic ester include styrene, α-methylstyrene, maleic anhydride, (meth)acrylonitrile, vinyl acetate, vinyl chloride, vinylpyrrolidone, and vinylpyridine.
[0043] The (meth)acrylic resin in the (meth)acrylic resin particles (C) is preferably a homopolymer of a (meth)acrylic acid ester, a copolymer of a (meth)acrylic acid ester, or a copolymer of a (meth)acrylic ester and a polymerizable monomer other than the (meth)acrylic ester, and more preferably a homopolymer of a (meth)acrylic acid ester or a copolymer of a (meth)acrylic acid ester. Among these, the (meth)acrylic resin particles (C) are particularly preferably crosslinked or non-crosslinked polymethyl methacrylate particles, in that the refractive index and haze can be easily adjusted.
[0044] The (meth)acrylic resin in the (meth)acrylic resin particles (C) may have a crosslinked structure or a non-crosslinked structure. When the (meth)acrylic resin has a crosslinked structure, the crosslinked structure may be formed by a known crosslinking agent such as a polyfunctional polymerizable monomer.
[0045] The average particle size of the (meth)acrylic resin particles (C) is not particularly limited. In terms of facilitating improved reworkability of the pressure-sensitive adhesive sheet and reduced haze, the average particle size of the (meth)acrylic resin particles (C) is preferably 0.1 to 5 μm, and more preferably 0.2 to 3 μm. The average particle size of the (meth)acrylic resin particles (C) refers to a value measured using a transmission electron microscope (TEM) or a scanning electron microscope (SEM). Specifically, one fine particle observed in a TEM image or SEM image of the pressure-sensitive adhesive sheet is randomly selected, and its maximum length (Dmax) and maximum perpendicular length (DV-max) are measured to obtain the geometric mean value of the fine particle (i.e., (Dmax×DV-max) 1 / 2 The geometric mean value of each of the 100 particles is calculated in the same manner, and the average value is determined as the average particle size of the (meth)acrylic resin particles (C) contained in the adhesive sheet. In other words, the average particle size of the (meth)acrylic resin particles (C) means the number-average particle size. The maximum length (Dmax) is the maximum length at two points on the contour of the particle image, and the maximum perpendicular length (DV-max) is the shortest length between two straight lines parallel to the maximum length when the particle image is sandwiched between these two straight lines.
[0046] The refractive index of the (meth)acrylic resin particles (C) is not particularly limited. In order to enhance the transparency of the pressure-sensitive adhesive sheet, the refractive index of the (meth)acrylic resin particles (C) is preferably 1.45 to 1.51, and more preferably 1.46 to 1.50.
[0047] More specifically, it is more preferable that the refractive index difference (absolute value) between the crosslinkable (meth)acrylic copolymer (A) and the (meth)acrylic resin particles (C) contained in the pressure-sensitive adhesive composition is 0 to 0.05, in which case the pressure-sensitive adhesive sheet can have better transparency.
[0048] The refractive index of the (meth)acrylic resin particles (C) referred to here indicates a value measured by method B described in JIS K 7142 (2014) “Plastics - Determination of refractive index”.
[0049] The (meth)acrylic resin particles (C) contained in the pressure-sensitive adhesive composition may be of one type only, or may be of two or more types.
[0050] The method for producing the (meth)acrylic resin particles (C) is not particularly limited, and for example, the (meth)acrylic resin particles (C) can be produced by a method similar to a known method. The (meth)acrylic resin particles (C) can also be obtained from commercial products.
[0051] <Crosslinking agent (D)> The crosslinking agent (D) may be a wide variety of components capable of promoting the crosslinking reaction of the crosslinkable (meth)acrylic copolymer (A). In particular, the crosslinking agent may be a wide variety of components capable of reacting with a carboxyl group or a hydroxyl group.
[0052] Such a crosslinking agent (D) can be selected from known crosslinking agents such as isocyanate compounds, epoxy compounds, oxazoline compounds, aziridine compounds, metal chelate compounds, and butylated melamine compounds.
[0053] Among them, the crosslinking agent (D) preferably contains one selected from the group consisting of an isocyanate compound, an epoxy compound, and a metal chelate. In this case, the resulting pressure-sensitive adhesive sheet can exhibit excellent reworkability and tends to have high transparency. When the crosslinking agent (D) contains a metal chelate, it is preferable to use a crosslinking retarder described below in combination.
[0054] Examples of the isocyanate compound include polyisocyanates such as tolylene diisocyanate, isophorone diisocyanate, chlorophenylene diisocyanate, diphenylmethane diisocyanate, butylene diisocyanate, hexamethylene diisocyanate, tetramethylene diisocyanate, hydrogenated diphenylmethane diisocyanate, and xylylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate and cyclohexylene diisocyanate; and aromatic isocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, and 4,4'-diphenylmethane diisocyanate. The isocyanate compound may be used alone or in a mixture of two or more different types. Examples of commercially available products include a tolylene diisocyanate compound (Coronate L, manufactured by Nippon Polyurethane Industry Co., Ltd.) and a xylylene diisocyanate compound (Takenate D-110N, manufactured by Mitsui Chemicals, Inc.).
[0055] Examples of epoxy compounds include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerin diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexanone, trimethylolpropane polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitol polyglycidyl ether, etc. Examples of commercially available epoxy compounds include TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.), TETRAD-X (manufactured by Mitsubishi Gas Chemical Co., Ltd.), etc.
[0056] Examples of the metal chelate compound include known metal chelate compounds used in crosslinking reactions, and examples of commercially available products include Aluminum Chelate A (manufactured by Kawaken Fine Chemicals).
[0057] <Adhesive composition> As described above, the pressure-sensitive adhesive composition contains the crosslinkable (meth)acrylic copolymer (A), the (meth)acrylic resin particles (C), and the crosslinking agent (D).
[0058] In the pressure-sensitive adhesive composition, the content of the (meth)acrylic resin particles (C) is not particularly limited, and may be, for example, 0.3 to 5 parts by mass, preferably 0.5 to 3 parts by mass, per 100 parts by mass of the total mass of the crosslinkable (meth)acrylic copolymer (A). In this case, the obtained pressure-sensitive adhesive sheet can have a small haze value while maintaining excellent reworkability.
[0059] In the pressure-sensitive adhesive composition, the content of the crosslinking agent (D) is not particularly limited, and can be, for example, 0.01 to 5 parts by mass per 100 parts by mass of the total mass of the crosslinkable (meth)acrylic copolymer (A). In this case, the processability of the obtained pressure-sensitive adhesive sheet is likely to be improved. The content of the crosslinking agent (D) can be 0.05 to 3 parts by mass per 100 parts by mass of the total mass of the crosslinkable (meth)acrylic copolymer (A).
[0060] The pressure-sensitive adhesive composition contains the crosslinkable (meth)acrylic copolymer (A), the (meth)acrylic resin particles (C), and the crosslinking agent (D) as described above, and may contain a solvent as necessary. When the pressure-sensitive adhesive composition contains a solvent, the coatability of the pressure-sensitive adhesive composition is improved, and the pressure-sensitive adhesive sheet can be easily formed.
[0061] Examples of the solvent include hydrocarbons such as hexane, heptane, octane, toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane; halogenated hydrocarbons such as dichloromethane, trichloroethane, trichloroethylene, tetrachloroethylene, and dichloropropane; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, and diacetone alcohol; ethers such as diethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, and ethyl butyrate; and polyols and derivatives thereof such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate.
[0062] The content of the solvent in the pressure-sensitive adhesive composition is not particularly limited, and is preferably 25 to 500 parts by mass, more preferably 30 to 400 parts by mass, relative to 100 parts by mass of the crosslinkable (meth)acrylic copolymer. In addition, the content of the solvent relative to the total mass of the pressure-sensitive adhesive composition is preferably 10 to 90% by mass, more preferably 20 to 80% by mass.
[0063] The pressure-sensitive adhesive composition may contain one type of solvent, or two or more types of solvents.
[0064] The adhesive composition may contain other components other than those described above, as long as the effects of the present invention are not impaired. Examples of other components include known components used as additives to adhesive compositions. Other components may be selected as needed from, for example, crosslinking retarders, plasticizers, antioxidants, metal corrosion inhibitors, tackifiers, silane coupling agents, ultraviolet absorbers, and light stabilizers such as hindered amine compounds. Dyes and pigments may also be added for coloring purposes.
[0065] Examples of the crosslinking retarder include acetylacetone. In particular, when the crosslinking agent (D) contains a metal chelate, it is preferable to use a crosslinking retarder in combination. Examples of the plasticizer include non-functional acrylic polymers. Examples of the non-functional acrylic polymers include polymers consisting of only acrylic monomer units having no functional groups other than acrylate groups, and polymers consisting of acrylic monomer units having no functional groups other than acrylate groups and non-acrylic monomer units having no functional groups. Since non-functional acrylic polymers do not crosslink, they can improve step conformability without affecting adhesion.
[0066] Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, lactone-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. These antioxidants may be used alone or in combination of two or more. As a metal corrosion inhibitor, benzoriazole-based resins are preferred because of their compatibility with the adhesive and their high effectiveness. Examples of the tackifier include rosin-based resins, terpene-based resins, terpene-phenol-based resins, coumarone-indene-based resins, styrene-based resins, xylene-based resins, phenol-based resins, and petroleum resins. Examples of the silane coupling agent include mercaptoalkoxysilane compounds (e.g., mercapto group-substituted alkoxy oligomers, etc.). Examples of the ultraviolet absorbing agent include benzotriazole-based compounds, benzophenone-based compounds, and triazine-based compounds.
[0067] When the pressure-sensitive adhesive composition contains other components, the content ratio thereof is not particularly limited and can be, for example, 15 parts by mass or less, preferably 10 parts by mass or less, per 100 parts by mass of the crosslinkable (meth)acrylic copolymer (A).
[0068] The method for preparing the pressure-sensitive adhesive composition is not particularly limited, and for example, any of the known methods for preparing pressure-sensitive adhesive compositions can be widely adopted.
[0069] <Composition and properties of adhesive sheet> The adhesive sheet of the present invention (hereinafter simply referred to as "adhesive sheet") is made of the cured product of the above-mentioned adhesive composition. That is, the adhesive sheet of the present invention can be obtained by curing the above-mentioned adhesive composition. The cured product of the adhesive composition can function as an adhesive layer in the adhesive sheet. The adhesive sheet can be composed of, for example, only an adhesive layer. That is, the adhesive sheet can also be formed of only a cured product of the adhesive composition. The adhesive layer can have a single-layer structure, or can have a multi-layer structure in which a plurality of single-layer adhesive layers are laminated. The adhesive sheet may be either a single-sided adhesive sheet or a double-sided adhesive sheet, and is preferably a double-sided adhesive sheet.
[0070] In an elastic modulus image of the adhesive sheet taken in Peak Force Tapping mode using an AFM, there are 3 to 20 spherical or island-like areas with a higher elastic modulus than the surroundings within any 10 μm square range. FIG. 2 shows an example of an elastic modulus image taken in Peak Force Tapping mode using an AFM on the surface of the adhesive sheet with an autoscaler using a tool with a measurable range of 0.01 GPa to 100 GPa. In FIG. 2, the spherical or island-like areas with a higher elastic modulus than the surroundings are shown in white, and the surrounding areas with a relatively lower elastic modulus are shown in black. Note that the relatively small white images such as dots and lines in FIG. 2 are considered to be images due to noise, and are not counted as spherical or island-like areas with a higher elastic modulus than the surroundings.
[0071] The number of the spherical or island-like portions having a higher elastic modulus than the surroundings is preferably 4 or more, more preferably 5 or more, and even more preferably 6 or more, from the viewpoint of particularly improving reworkability, and is preferably 16 or less, more preferably 13 or less, and even more preferably 10 or less, from the viewpoint of particularly improving transparency.
[0072] The number of spherical or island-like portions having a higher elastic modulus than the surrounding area can be measured by the following method. First, an elastic modulus image is taken of the surface of the adhesive sheet in Peak Force Tapping mode using an AFM by the following method. Equipment used: MultiMode8 (Bruker Nano) <Peak Force Tappingモード> Cantilever: ScanAsyst-Air Scan Size: 10μm square Gain:Auto Setpoint: 10μm square_4.0nN Sync Distance: 75.0 Using the above method, 10 different fields of view are observed to prepare 10 elasticity images. In each elasticity image, the number of spheres or islands with a higher elasticity than the surroundings is measured by visually counting the number of white spheres or islands. The average of the 10 elasticity images is calculated as the measured value of the number of spheres or islands with a higher elasticity than the surroundings.
[0073] The elastic modulus of the spherical or island-shaped portion having a higher elastic modulus than the surrounding area is relatively higher than the surrounding area, and the elastic modulus is preferably 1 GPa or more, more preferably 5 GPa or more. The upper limit of the elastic modulus is not particularly limited, and may be about 60 GPa. The elastic modulus of the surrounding area having a relatively lower elastic modulus other than the spherical or island-shaped portion having a higher elastic modulus than the surrounding area is preferably less than 1 GPa, more preferably 0.5 GPa or less, even more preferably 0.1 GPa or less, and particularly preferably 0.05 GPa or less. The lower limit of the elastic modulus is not particularly limited, and may be less than -0.01 GPa.
[0074] The elastic modulus of a spherical or island-shaped portion having a higher elastic modulus than its surroundings is preferably at least 10 times the elastic modulus of the surrounding portions having a relatively lower elastic modulus other than the spherical or island-shaped portion having a higher elastic modulus than its surroundings.
[0075] The elastic modulus can be measured by analyzing an elastic modulus image of the surface taken in Peak Force Tapping mode using the AFM described above, using software provided with the device used.
[0076] <Physical properties of adhesive sheet> (Physical Properties 1) The pressure-sensitive adhesive sheet satisfies the following physical property (1). Physical properties (1): The adhesive strength to glass 30 minutes after application, measured according to the adhesive strength measuring method described in JIS Z 0237, is 0.01 to 5 N / 25 mm.
[0077] In the physical property (1), when measuring the adhesive strength of the adhesive sheet to glass, the adhesive strength to glass is measured 1 minute after lamination to glass according to the method for measuring adhesive strength described in JIS Z 0237. More specifically, 100 μm PET (manufactured by Toyobo Co., Ltd. / product number: Cosmoshine A4300) is laminated to one side of the adhesive sheet, and then this is treated in an autoclave at 100°C and 0.5 MPa (meaning gauge pressure) for 30 minutes. The adhesive sheet having a PET substrate on one side thus treated is laminated to soda glass (Hiraoka Special Glass Manufacturing Co., Ltd., the pressure-bonded surface is the opposite side to the tin float). At this time, a measurement sample is prepared according to the method for measuring 180° peel adhesive strength described in JIS Z 0237, except that soda glass is used as the test plate. Then, the adhesive strength is measured 1 minute after lamination at a peel speed of 300 mm / min. This adhesive strength is the adhesive strength to glass in the physical property (1).
[0078] In physical property (1), the adhesive strength to glass is preferably 0.05 N / 25 mm or more, since this particularly improves reworkability. Also, the adhesive strength to glass in physical property (1) is preferably 4.8 N / 25 mm or less, more preferably 4.6 N / 25 mm or less, and even more preferably 4.5 N / 25 mm or less.
[0079] The adhesive strength to glass in the physical property (1) can be adjusted by adjusting the types and ratio of the constituent units of the crosslinkable (meth)acrylic copolymer, the average particle size and amount of the (meth)acrylic resin particles (C), and the amount of the crosslinking agent (D).
[0080] (Physical Properties 2) The pressure-sensitive adhesive sheet satisfies the following physical property (2). Physical property (2): The adhesive sheet is attached to a glass plate and heat-treated for 30 minutes at 100°C and 0.5 MPa (gauge pressure), after which the adhesive strength to glass measured in accordance with the adhesive strength measuring method described in JIS Z 0237 is 10 N / 25 mm or more.
[0081] In physical property (2), when measuring the adhesive strength of the adhesive sheet to glass, a measurement sample is prepared in the same manner as in physical property (1). The measurement sample is then treated in an autoclave at 100°C and 0.5 MPa for 30 minutes, and then left to stand for 2 hours in an environment of 23°C and 50% relative humidity. The adhesive strength is then measured at a peeling speed of 300 mm / min in the same manner as in physical property (1). This adhesive strength is regarded as the adhesive strength to glass in physical property (2).
[0082] In physical property (2), the adhesive strength to glass is preferably 10 N / 25 mm or more, more preferably 15 N / 25 mm or more, even more preferably 20 N / 25 mm or more, and particularly preferably 25 N / 25 mm or more, in order to increase the adhesive strength to the adherend after heat treatment. The adhesive strength to glass in physical property (2) is not particularly limited, and is preferably 50 N / 25 mm or less in order to facilitate disposal or dismantling of displays, etc.
[0083] The adhesive strength to glass in the physical property (2) can be adjusted by adjusting the types and ratio of the constituent units of the crosslinkable (meth)acrylic copolymer, the average particle size and amount of the (meth)acrylic resin particles (C), and the amount of the crosslinking agent (D).
[0084] In view of the tendency of the pressure-sensitive adhesive sheet to have high transparency, the pressure-sensitive adhesive sheet of the present invention preferably has a haze of 0 to 2%, more preferably 1.9% or less, and even more preferably 1.8% or less, measured in accordance with JIS K 7136. The haze value may be 0%.
[0085] The haze of the adhesive sheet is measured according to JIS K 7136. Specifically, a pair of transparent glass plates (S9112, manufactured by Matsunami Glass Industry Co., Ltd.) having a thickness of 1.2 mm is laminated with an adhesive sheet to prepare a laminated sample, and the laminated sample is used to measure the haze according to JIS K7136 (2000). A haze meter NDH7000 manufactured by Nippon Denshoku Industries Co., Ltd. can be used for this measurement. The laminated sample is prepared, for example, as follows. The release sheet on the light release side of the adhesive sheet with release sheet is peeled off and laminated to one transparent glass plate, and then the other transparent glass plate is laminated to the surface from which the release sheet (heavy release separator) on the heavy release side is peeled off so as not to allow air to be mixed in. This is treated in an autoclave under conditions of 100°C and 0.5 MPa (meaning gauge pressure) for 30 minutes, and then left to stand for 2 hours in an environment of 23°C and relative humidity of 50%, to obtain a laminated sample.
[0086] The haze value can be adjusted by adjusting the type and ratio of the constituent units of the crosslinkable (meth)acrylic copolymer, as well as the refractive index, average particle size and amount of the (meth)acrylic resin particles (C).
[0087] Since the pressure-sensitive adhesive sheet has the above-mentioned physical property (1), the initial adhesive strength is not too strong, and therefore the position adjustment ability (reworkability) is excellent. Therefore, when the pressure-sensitive adhesive sheet of the present invention is used for bonding components together, such as for bonding optical components, the pressure-sensitive adhesive sheet can be easily peeled off from the optical component, so that re-bonding can be easily performed, and adhesive residue derived from the pressure-sensitive adhesive sheet is unlikely to occur.
[0088] Since the adhesive sheet has the above-mentioned physical property (2), the adhesive strength can be increased by bonding the members together and then heating them. This makes it possible to firmly bond the adherends together. Thus, the adhesive sheet of the present invention has succeeded in keeping the initial adhesive strength low while increasing the adhesive strength after heating, and thus combines two opposing adhesive properties.
[0089] Furthermore, the adhesive sheet has 3 to 20 spherical or island-shaped parts with higher elastic modulus than the surroundings in an elastic modulus image measured under specific conditions using an AFM, so that it is possible to simultaneously exhibit high reworkability, strong adhesion after heating, and high transparency. Therefore, the adhesive sheet of the present invention is also suitable for use in optical applications and the like that require high transparency and reworkability.
[0090] As described above, the pressure-sensitive adhesive sheet of the present invention has the physical properties (1) and (2), and the number of spherical or island-like parts having a higher elastic modulus than the surroundings in the elastic modulus image measured under specific conditions using an AFM is 3 to 20, so that the pressure-sensitive adhesive sheet can be given reworkability and high transparency, and the pressure-sensitive adhesive sheet can achieve both transparency and reworkability, which have been in a trade-off relationship in the past. Furthermore, the pressure-sensitive adhesive sheet of the present invention does not peel off even after the passage of time after lamination, and has excellent stability over time.
[0091] <Other properties of adhesive sheets> The thickness of the pressure-sensitive adhesive sheet is not particularly limited as it can be appropriately set depending on the application, and is, for example, preferably 5 to 300 μm, more preferably 8 to 200 μm, and particularly preferably 10 to 150 μm.
[0092] The gel fraction of the pressure-sensitive adhesive sheet is not particularly limited, and can be appropriately set depending on the components and types contained in the pressure-sensitive adhesive sheet. For example, the gel fraction of the pressure-sensitive adhesive sheet is 35 to 100%, preferably 40 to 95%, and more preferably 45 to 90%. The above gel fraction is the gel fraction before the pressure-sensitive adhesive sheet is heated, but since the change in gel fraction before and after heating is small in the pressure-sensitive adhesive sheet of the present invention, it is preferable that the gel fraction of the pressure-sensitive adhesive sheet after heat treatment for 30 minutes under conditions of 100°C and 0.5 MPa is also within the above range.
[0093] The gel fraction of the adhesive layer is a value measured by the following method. First, about 0.1 g of the adhesive sheet (adhesive layer) is collected in a sample bottle, 30 ml of ethyl acetate is added, and the mixture is shaken for 24 hours. The contents of the sample bottle are then filtered through a 150 mesh stainless steel wire screen, and the residue on the wire screen is dried at 100°C for 1 hour to measure the dry mass (g). The gel fraction is calculated from the obtained dry mass using the following formula 1. Gel fraction (mass%) = (dry mass / collected mass of adhesive sheet) × 100 Equation 1
[0094] <How to use the adhesive sheet> The method of using the adhesive sheet of the present invention is not particularly limited, and for example, the same method of use as known adhesive sheets can be adopted.When the adhesive sheet of the present invention is the above-mentioned heat-adhesive sheet, the adhesive sheet can be used by contacting the adhesive sheet of the present invention with the surface of the adherend and then heating the adhesive sheet.By heating in this way, the adhesive sheet can be made to adhere to the adherend more closely.In addition, since the adhesive sheet has excellent reworkability, the position of the adhesive sheet before heating can be easily adjusted.
[0095] The pressure-sensitive adhesive sheet is heated after contacting the surface of the adherend at, for example, 50 to 120° C. The heating time can be appropriately set according to the heating temperature, for example, 1 to 120 minutes. Pressure may be applied during the heat treatment, and it is preferable to apply a pressure of, for example, 0.2 to 0.9 MPa. By carrying out such a heat treatment, the adhesive strength of the pressure-sensitive adhesive sheet is significantly increased, and the sheet adheres more firmly to the adherend.
[0096] <Adhesive sheet with release sheet> An adhesive sheet with a release sheet can also be formed from the adhesive sheet of the present invention, as shown in Figure 1. An adhesive sheet with a release sheet 10 can have release sheets 12a and 12b on both surfaces of an adhesive layer 11 (adhesive sheet).
[0097] As the release sheet, for example, a wide variety of known release sheets can be used, including a release laminate sheet formed by forming a release agent layer on one side of a release sheet substrate, and other low-polarity substrates formed of polyolefin films such as polyethylene films and polypropylene films. For example, papers and polymer films are used as the release sheet substrate.
[0098] As the release agent constituting the release agent layer, for example, a general-purpose addition type or condensation type silicone-based release agent or a compound containing a long chain alkyl group is used. In particular, an addition type silicone-based release agent having high reactivity is preferably used. Specific examples of the silicone-based release agent include BY24-4527 and SD-7220 manufactured by Toray Dow Corning Silicone Co., Ltd., and KS-3600, KS-774, and X62-2600 manufactured by Shin-Etsu Chemical Co., Ltd. In addition, the silicone-based release agent includes a silicone-based release agent having a SiO2 unit and a (CH3)3SiO 1 / 2 Unit or CH2=CH(CH3)SiO 1 / 2 It is also preferable to contain a silicone resin, which is an organosilicon compound having a unit. Specific examples of silicone resins include BY24-843, SD-7292, SHR-1404, etc. manufactured by Dow Corning Toray Silicone Co., Ltd., and KS-3800, X92-183, etc. manufactured by Shin-Etsu Chemical Co., Ltd.
[0099] The peelable laminate sheet can be obtained commercially, for example, a heavy separator film which is a release-treated polyethylene terephthalate film manufactured by Teijin DuPont Films Co., Ltd., or a light separator film which is a release-treated polyethylene terephthalate film manufactured by Teijin DuPont Films Co., Ltd.
[0100] The adhesive sheet with release sheet preferably has a pair of release sheets with different release strengths on both surfaces of the adhesive sheet. That is, the release sheets preferably have different releasability between release sheet 12a and release sheet 12b to facilitate peeling. If the releasability from one side is different from the releasability from the other side, it becomes easier to peel off only the release sheet with higher releasability (light release side) before the heavy release side.
[0101] <Applications of adhesive sheets> The pressure-sensitive adhesive sheet of the present invention can be used for various applications, for example, for bonding optical members used in optical devices and the like.
[0102] Examples of optical members include components of optical products such as touch panels, image display devices, etc. Examples of components of touch panels include an ITO film in which an ITO film is provided on a transparent resin film, an ITO glass in which an ITO film is provided on the surface of a glass plate, a transparent conductive film in which a conductive polymer is coated on a transparent resin film, a hard coat film, and a fingerprint-resistant film.
[0103] Examples of components of image display devices include anti-reflection films, alignment films, polarizing films, retardation films, brightness enhancement films, etc., which are used in liquid crystal display devices. The pressure-sensitive adhesive sheet of the present invention may also be used for bonding modules such as a liquid crystal module and a touch panel module.
[0104] Specific examples of materials that can be bonded with an adhesive sheet include glass, polycarbonate, polyethylene terephthalate, polymethyl methacrylate, polyethylene naphthalate, cycloolefin polymer, triacetyl cellulose, polyimide, and cellulose acylate.
[0105] 2. Manufacturing method of adhesive sheet The method for producing the pressure-sensitive adhesive sheet of the present invention is not particularly limited, and known methods can be widely adopted.Among them, it is preferable to form the pressure-sensitive adhesive sheet by a production method including a step of forming a coating film by applying the above-mentioned pressure-sensitive adhesive composition on a release sheet, and a step of heating this coating film.In such a production method, when the pressure-sensitive adhesive composition contains a solvent, the solvent is removed in the heating step, and at the same time, the reaction of the crosslinkable (meth)acrylic copolymer and the crosslinking agent proceeds to form a cured product (pressure-sensitive adhesive layer).
[0106] The pressure-sensitive adhesive composition can be applied using a known coating device, such as an applicator, a blade coater, an air knife coater, a roll coater, a bar coater, a gravure coater, a microgravure coater, a rod blade coater, a lip coater, a die coater, or a curtain coater.
[0107] The substrate used for coating the adhesive composition is not particularly limited. For example, the adhesive composition can be coated on various substrates such as a resin substrate, a glass substrate, etc. For example, when obtaining an adhesive sheet with a release sheet, a release sheet can be selected as the substrate. The adhesive composition can also be directly coated on the member to be bonded.
[0108] The thickness of the pressure-sensitive adhesive composition after coating is not particularly limited, and can be appropriately set depending on the desired thickness of the pressure-sensitive adhesive layer.
[0109] In the step of heating the coating film, the heating temperature is not particularly limited, and is preferably, for example, 50 to 150°C. The heating time can be appropriately adjusted depending on the heating temperature, the thickness of the coating film, and the content of the solvent in the pressure-sensitive adhesive composition, and can be, for example, 1 to 60 minutes. A known heating device such as a heating furnace or an infrared lamp can be used to heat the coating film. After heating, it is preferable to carry out an aging treatment in which the pressure-sensitive adhesive sheet is left to stand at a constant temperature for a certain period of time. The aging treatment can be carried out, for example, by leaving the sheet to stand at 23°C for 7 days.
[0110] 3.Laminate The laminate of the present invention comprises the pressure-sensitive adhesive sheet of the present invention and an adherend. When the pressure-sensitive adhesive sheet is a double-sided pressure-sensitive adhesive sheet, the adherend is preferably provided directly on both sides of the pressure-sensitive adhesive sheet. In this case, the laminate has a structure in which the adherend / pressure-sensitive adhesive sheet / adherend are laminated in this order. The adherend can be, for example, the optical member described above.
[0111] The laminate of the present invention can be applied to various applications, and can be suitably used, for example, in optical devices, image display devices, etc. In particular, since the laminate of the present invention is formed by bonding with a highly transparent pressure-sensitive adhesive sheet, when applied to optical devices, image display devices, etc., the design and visibility of the image can be further improved. EXAMPLES
[0112] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples.
[0113] [Synthesis of crosslinkable (meth)acrylic copolymer A-1] Monomers prepared by mixing butyl acrylate (BA), acrylic acid (AA) and methyl methacrylate macromonomer (AA-6, number average molecular weight 6000, manufactured by Toagosei Co., Ltd.) in a mass ratio of 94:3:3 were polymerized in the presence of AIBN (azobisisobutyronitrile) in ethyl acetate, a polymerization solvent, by heating to 60°C. This resulted in a solution of crosslinkable (meth)acrylic copolymer (A-1) (represented as "A-1" in Table 1) with a solid content concentration of 30% by mass and a weight average molecular weight of 720,000.
[0114] [Synthesis of crosslinkable (meth)acrylic copolymer A-2] A monomer mixture of BA, 2-hydroxyethyl acrylate (2HEA) and a methyl methacrylate macromonomer (AA-6, number average molecular weight 6000, manufactured by Toagosei Co., Ltd.) in a mass ratio of 70:20:10 was polymerized by heating to 60°C in the presence of AIBN (azobisisobutyronitrile) in ethyl acetate, a polymerization solvent. This resulted in a solution of a crosslinkable (meth)acrylic copolymer (A-2) (represented as "A-2" in Table 1) with a solid content concentration of 35% by mass and a weight average molecular weight of 600,000.
[0115] Example 1 [Preparation of Adhesive Composition] The raw materials, which include 1 part by mass of MX-80H3WT (average particle size 0.8 μm, manufactured by Soken Chemical Industries, Ltd.) as the (meth)acrylic resin particles (C), 0.1 parts by mass and 0.5 parts by mass of an epoxy compound (Tetrad X, manufactured by Mitsubishi Gas Chemical Co., Ltd.) and a metal chelate compound (Aluminum Chelate A, manufactured by Kawaken Fine Chemicals Co., Ltd.) as crosslinking agents, 5 parts by mass of acetylacetone (manufactured by Tokyo Chemical Industry Co., Ltd.) as a crosslinking retarder, and 0.5 parts by mass of a silane coupling agent (KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts by mass of the acrylic copolymer (A-1), were added to ethyl acetate so that the concentration of the raw materials was 25% by mass, and stirred to prepare a pressure-sensitive adhesive composition a-1.
[0116] [Preparation of adhesive sheet] The adhesive composition a-1 prepared as described above was uniformly applied with an applicator to the surface of a 50 μm thick polyethylene terephthalate film (first release sheet, Oji F-Tex Co., Ltd., 50RL-07(2)) having a release agent layer treated with a silicone-based release agent, so that the coating thickness after drying was 25 μm, forming a coating film. The coating film was dried at 100° C. for 3 minutes in an air-circulating thermostatic oven, forming an adhesive layer (adhesive sheet) on the surface of the first release sheet.
[0117] Next, a 38 μm thick second release sheet (Oji F-Tex Co., Ltd., 38RL-07(L)) with a release strength different from that of the first release sheet was attached to the surface of the adhesive layer, and cured for 14 days under conditions of 23° C. and a relative humidity of 50%. This resulted in an adhesive sheet with release sheet having a first release sheet / adhesive sheet / second release sheet configuration in which the adhesive layer (adhesive sheet) was sandwiched between a pair of release sheets with different release strengths.
[0118] Example 2 An adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the (meth)acrylic resin particles (C) were changed to MX-300 (average particle size 3 μm, manufactured by Soken Chemical & Engineering Co., Ltd.).
[0119] Example 3 Raw materials containing 1.5 parts by mass of XX-5910 (average particle size 0.3 μm, manufactured by Sekisui Chemical Co., Ltd.) as (meth)acrylic resin particles (C), 0.1 parts by mass of an isocyanate compound (Coronate L-55, manufactured by Tosoh Corporation) as a crosslinking agent, and 0.5 parts by mass of a silane coupling agent (KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts by mass of the acrylic copolymer (A-2) were added to ethyl acetate so that the concentration of the raw materials was 27% by mass, and stirred to prepare a pressure-sensitive adhesive composition a-2.
[0120] Next, a pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the pressure-sensitive adhesive composition a-1 was changed to the pressure-sensitive adhesive composition a-2.
[0121] Example 4 An adhesive sheet with a release sheet was obtained using the same procedure as in Example 3, except that the (meth)acrylic resin particles (C) were changed to BMSA-18GN (average particle size 0.8 μm, manufactured by Sekisui Chemical Co., Ltd.) and the amount used was changed to 2 parts by mass.
[0122] Example 5 A pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 4, except that the amount of (meth)acrylic resin particles (C) used was changed to 0.5 parts by mass.
[0123] Comparative Example 1 An adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the adhesive composition was prepared without using the (meth)acrylic resin particles (C).
[0124] Comparative Example 2 An adhesive sheet with a release sheet was obtained in the same manner as in Example 3, except that the (meth)acrylic resin particles (C) were replaced with melamine resin particles Eposter M30 (average particle size 3 μm, manufactured by Nippon Shokubai Co., Ltd.).
[0125] Comparative Example 3 An adhesive sheet with a release sheet was obtained using the same procedure as in Example 3, except that the (meth)acrylic resin particles (C) were changed to MBX-20 (average particle size 20 μm, manufactured by Sekisui Chemical Co., Ltd.) and the amount used was changed to 1 part by mass.
[0126] [Physical property 1: Adhesion to glass] The adhesive strength was measured according to the method for measuring adhesive strength described in JIS Z 0237. First, the release sheet on the light release side of the adhesive sheet with release sheet was peeled off and laminated with 100 μm PET (manufactured by Toyobo Co., Ltd. / product number: Cosmoshine A4300), and then treated in an autoclave at 100°C and 0.5 MPa (gauge pressure) for 30 minutes to obtain an adhesive sheet having a PET substrate on one side. The release sheet on the heavy release side of this adhesive sheet having a PET substrate on one side was peeled off and laminated to soda glass (Hiraoka Special Glass Manufacturing Co., Ltd., the pressure-bonded surface was the opposite side to the tin float). At this time, a measurement sample was prepared according to the method for measuring 180° peel adhesive strength described in JIS Z 0237, except that soda glass was used as the test plate. Then, the adhesive strength was measured at a peel speed of 300 mm / min 1 minute after pressure bonding, and this adhesive strength was taken as the adhesive strength to glass in physical property (1).
[0127] [Physical property 2: Adhesion to glass] A measurement sample was prepared in the same manner as in the physical property 1, up to the step of bonding to the test plate. After that, this measurement sample was treated for 30 minutes under conditions of 100°C and 0.5 MPa (gauge pressure) using an autoclave, and then left to stand for 2 hours in an environment of 23°C and 50% relative humidity. Then, the adhesive strength was measured at a peeling speed of 300 mm / min in the same manner as in the physical property (1), and this adhesive strength was taken as the adhesive strength to glass in the physical property (2).
[0128] [Measuring the number of spherical or island-like areas using AFM] First, an elastic modulus image was taken of the surface of the pressure-sensitive adhesive sheet in Peak Force Tapping mode using an AFM by the following method. Equipment used: MultiMode8 (Bruker Nano) <Peak Force Tappingモード> Cantilever: ScanAsyst-Air Scan Size: 10μm square Gain:Auto Setpoint: 10μm square_4.0nN Sync Distance: 75.0 Using the above method, 10 different fields of view were observed to prepare 10 elasticity images. In each elasticity image, the number of spheres or islands with a higher elasticity than the surroundings was measured by visually counting the number of white spheres or islands. The average value of the 10 elasticity images was calculated as the measured value of the number of spheres or islands with a higher elasticity than the surroundings.
[0129] [Weight average molecular weight] The weight average molecular weight of the crosslinkable (meth)acrylic copolymer (A) was measured by gel permeation chromatography (GPC) under the following conditions. Solvent: Tetrahydrofuran Column: Shodex KF801, KF803L, KF800L, KF800D (four columns made by Showa Denko K.K. were used in combination) Column temperature: 40℃ Sample concentration: 0.5% by mass Detector: RI-2031plus (JASCO) Pump: RI-2080plus (JASCO) ·Flow rate (flow rate): 0.8ml / min ·Injection volume: 10μl Calibration curve: A calibration curve was used using 10 samples of standard polystyrene (Shodex standard polystyrene, manufactured by Showa Denko K.K.) with Mw=1320 to 2,500,000.
[0130] [Refractive index measurement] The refractive index of the crosslinkable (meth)acrylic copolymer (A) was measured in accordance with Method A described in JIS K 7142 (2014) "Plastics - Determination of refractive index." The refractive index of the (meth)acrylic resin particles (C) was measured in accordance with Method B described in JIS K 7142 (2014) "Plastics - Determination of refractive index."
[0131] (Evaluation of adhesive sheets) The pressure-sensitive adhesive sheets obtained in each of the Examples and Comparative Examples were evaluated according to the following procedures.
[0132] [Position adjustability (reworkability)] A test piece was obtained by cutting the adhesive sheet having a PET substrate on one side obtained in the process of preparing a measurement sample for physical property (1) to a size of 50 mm x 60 mm. The test piece was pressed onto a float glass sheet (manufactured by Nippon Sheet Glass Co., Ltd.) of 30 mm x 40 mm (thickness 10 mm) using a hand roller so that the center point of the float glass sheet and the center point of the adhesive sheet overlap each other to prepare a laminate. The laminate was placed on a horizontal table in an environment of 23 ° C. and relative humidity 50% so that the adhesive sheet side faced the table and was pressed. Within 1 minute after pressing, the adhesive sheet protruding from the glass plate was lightly pressed with one hand, while the glass plate was picked up with the other hand and the glass plate was peeled upward from the adhesive sheet. The peelability at this time was evaluated according to the following criteria. ○: Easy to peel off and has excellent reworkability. ×: Not peelable or difficult to peelable (for example, it cannot be peeled unless the adhesive sheet side is placed up and the adhesive sheet is pulled up from the edge to be peeled off), poor reworkability.
[0133] [Whether or not peeling occurs over time] The laminate prepared in the process of evaluating the position adjustability (reworkability) was treated for 240 hours using a thermohygrostat at 65°C (relative humidity 95%), and then left to stand for 60 minutes in an environment of 23°C and relative humidity 50%. Thereafter, it was visually evaluated according to the following criteria. ○: No peeling or lifting occurs ×: Peeling or lifting occurs at edges, etc.
[0134] [Image design and visibility] The release sheet on the light release side of the adhesive sheet with release sheet was peeled off, and the adhesive sheet was laminated with 100 μm PET (manufactured by Toyobo Co., Ltd. / product number: Cosmoshine A4300), and the adhesive sheet was cut into a size of 150 mm × 70 mm to obtain a test piece. Next, the release sheet on the heavy release side of this test piece was peeled off, and the entire exposed surface was laminated with the surface opposite to the black printed surface of a 150 mm × 70 mm (thickness 6 mm) float plate glass (manufactured by Nippon Sheet Glass Co., Ltd.) having a black printed surface, using a hand roller to obtain a laminated sample. The obtained laminate was treated in an autoclave under conditions of 100 ° C. and 0.5 MPa (gauge pressure) for 30 minutes, and then left to stand for 2 hours in an environment of 23 ° C. and relative humidity 50%, to prepare an evaluation sample. Apart from this evaluation sample, a float plate glass similar to the float plate glass used to prepare the evaluation sample was prepared as a blank. The PET surface of the evaluation sample was visually compared with the glass surface opposite the black printed surface of the blank product, and the design and visibility of the image were evaluated based on the following criteria. ○: Blackness and glossiness similar to that of the blank product. △: Slightly less black and glossy than the blank product. ×: Inferior blackness and glossiness compared to the blank product.
[0135] [Haze] The haze of the adhesive sheet was measured in accordance with JIS K 7136. Specifically, a pair of transparent glass plates (S9112, manufactured by Matsunami Glass Industry Co., Ltd.) having a thickness of 1.2 mm was laminated with an adhesive sheet to prepare a laminated sample, and the laminated sample was used to measure the haze in accordance with JIS K7136 (2000). A haze meter NDH7000 manufactured by Nippon Denshoku Industries Co., Ltd. was used for the measurement. The laminated sample was prepared as follows. First, the release sheet on the light release side of the adhesive sheet with release sheet was peeled off and laminated to one transparent glass plate, and then the other transparent glass plate was laminated to the surface from which the release sheet (heavy release separator) on the heavy release side was peeled off so as not to allow air to be mixed in. This was treated in an autoclave under conditions of 100°C and 0.5 MPa (gauge pressure) for 30 minutes, and then left to stand for 2 hours in an environment of 23°C and relative humidity of 50% to obtain a laminated sample.
[0136] [Table 1]
[0137] Table 1 shows the preparation conditions for the pressure-sensitive adhesive sheets of the above-mentioned Examples and Comparative Examples, as well as the physical properties and evaluation results of each pressure-sensitive adhesive sheet. In Table 1, "(A)-(C) refractive index difference" means the refractive index difference (absolute value) between the crosslinkable (meth)acrylic copolymer (A) and the (meth)acrylic resin particles (C).
[0138] From Table 1, it was found that the pressure-sensitive adhesive sheets obtained in the examples had excellent reworkability and low haze, i.e., excellent transparency. Moreover, the pressure-sensitive adhesive sheets obtained in the examples did not peel off even after time had passed after lamination, and had excellent stability over time. Furthermore, it was found that the laminates produced using the pressure-sensitive adhesive sheets obtained in the examples had excellent image design and visibility, and therefore were suitable for use in image display devices and the like. [Explanation of symbols]
[0139] 10. Adhesive sheet with release sheet 11 Adhesive layer 12a Release sheet 12b Release sheet
Claims
1. In a pressure-sensitive adhesive sheet formed from a cured product of a pressure-sensitive adhesive composition, The pressure-sensitive adhesive composition contains a crosslinkable (meth)acrylic copolymer (A), (meth)acrylic resin particles (C), and a crosslinking agent (D), The crosslinkable (meth)acrylic copolymer (A) is a polymer including (meth)acrylic ester units (a) having an alkyl group having 4 to 10 carbon atoms, monomer units (b) having a carboxy group and / or a hydroxyl group, and macromonomer units (c) having a methyl methacrylate unit; the crosslinkable (meth)acrylic copolymer (A) contains 50 to 95 mass% of the (meth)acrylic ester unit (a), 1 to 50 mass% of the monomer unit (b), and 1 to 15 mass% of the macromonomer unit (c), and the content of other structural units than the (meth)acrylic ester unit (a), the monomer unit (b), and the macromonomer unit (c) is 15 mass% or less with respect to the total mass of the crosslinkable (meth)acrylic copolymer (A); The (meth)acrylic resin particles (C) have an average particle size of 0.1 to 5 μm, In an elastic modulus image taken of the surface in Peak Force Tapping mode using an atomic force microscope, there are 3 to 20 spherical or island-like areas having a higher elastic modulus than the surrounding areas within any 10 μm square range, A pressure-sensitive adhesive sheet that satisfies the following physical properties (1) and (2). Physical properties (1): The adhesive strength to glass one minute after application, measured according to the adhesive strength measuring method described in JIS Z 0237, is 0.01 to 5 N / 25 mm. Physical property (2): The adhesive sheet is applied to a glass plate and heat-treated at 100° C. and 0.5 MPa for 30 minutes. The adhesive strength to glass measured according to the adhesive strength measuring method described in JIS Z 0237 is 10 N / 25 mm or more.
2. The pressure-sensitive adhesive sheet according to claim 1, wherein the macromonomer unit (c) has a number average molecular weight of 5,000 to 10,000.
3. 3. The pressure-sensitive adhesive sheet according to claim 1, wherein a refractive index difference between the crosslinkable (meth)acrylic copolymer (A) and the (meth)acrylic resin particles (C) is 0 to 0.
05.
4. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein the crosslinking agent (D) comprises one selected from the group consisting of an isocyanate compound, an epoxy compound, and a metal chelate.
5. A laminate comprising the pressure-sensitive adhesive sheet according to any one of claims 1 to 4 and an adherend.
6. An optical device comprising the laminate according to claim 5 .
7. An image display device comprising the laminate according to claim 5 .
Citation Information
Patent Citations
Readily peelable pressure-sensitive adhesive sheet and its manufacture
JP1992100879A
Adhesive sheet for cleaning screen printing plate
JP2001199053A
Adhesive type optical film
JP2002212526A
Pressure-sensitive adhesive sheet and pressure-sensitive adhesive composition
JP2013221073A
Adhesive sheet
JP2015003943A